1997
DOI: 10.1097/00003246-199711000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Brief episodes of ventricular fibrillation do not influence postischemic cerebral perfusion assessed by positron emission tomography

Abstract: Short episodes of ventricular fibrillation did not induce any measurable effects on global and regional cerebral perfusion detectable by positron emission tomography 30 secs and 10 mins after restitution of sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Transcranial Doppler studies have also shown a delayed recovery of cerebral blood flow after induced VT or VF 2,27,28 . Although our recovery times did not correlate with the duration of time in CA, they were similar to those detected by positron‐emission tomography following the restitution of sinus rhythm 29 . All parameters were restored to baseline levels by 30 seconds.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Transcranial Doppler studies have also shown a delayed recovery of cerebral blood flow after induced VT or VF 2,27,28 . Although our recovery times did not correlate with the duration of time in CA, they were similar to those detected by positron‐emission tomography following the restitution of sinus rhythm 29 . All parameters were restored to baseline levels by 30 seconds.…”
Section: Discussionsupporting
confidence: 70%
“…2,27,28 Although our recovery times did not correlate with the duration of time in CA, they were similar to those detected by positron-emission tomography following the restitution of sinus rhythm. 29 All parameters were restored to baseline levels by 30 seconds. Murkin et al advocated a reperfusion interval of greater than 4 minutes between successful defibrillation and subsequent DFT tests to minimize the potential for postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%